Misventure in the Treacherous Terrain of Subscapularis during Latarjet Procedure: A Case Report - Sathyakumar, Kirthi; Kandagaddala, Madhavi; Sasi, Kiran; Ashok, Anand; Chinniah, Praveen K. (Indian Journal of Radiology and Imaging, 2025)
Latarjet procedure is one of the commonly performed surgeries for recurrent anterior dislocation of the shoulder and has been modified by many surgeons over the past eight decades. This procedure mandates detailed understanding of the anatomy of the shoulder, axillary region, and brachial plexus, as the subscapularis muscle will be split open during the procedure, which forms the bed for axillary artery and cords and branches of the brachial plexus. Any deviation from the procedure could lead to untoward complications. We present an extremely rare case of injury to the lateral cord of brachial plexus, musculocutaneous nerve, and median nerve following the Latarjet procedure.
Keywords: brachial plexus injury; Latarjet procedure; subscapularis splitting method